Responding to drought in Malawi - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
A senior agricultural officer describes the steps being taken by the extension services in Malawi to enable farmers overcome the challenge of drought